CRITICISM IN ENGLISH LITERATURE: A REVIEW OF INTERNATIONAL EVIDENCE - Marannu Eppang (Al-Qanṭara, 2022)
Abstract The English literary-critical tradition finds its origins in a specific bi-lingual sensibility that dominated the literary critical scene after the arrival of the British. The Renaissance period for the development and advancement of such a tradition was the eighteenth century. The main products of this bi-lingual sensibility were conveyed by the preachers themselves, who were mostly British, and were used in the administration of the East India Company as translations into English of sacred writings and other sacred writings. This also included verifiable and religious records. A brief introduction to the history of criticism will be provided at the outset. The sign of the word "Literary Criticism" alongside the beginning and progression of Literary Criticism must then be examined. There are numerous ways in which criticism can be classified. There are several major critical hypotheses, such as mimetic, pragmatic, expressive, and objective. Aristotelian versus Non-romantic is a common polarity in criticism. Aristotelian criticism implies a legal, intelligent, formal criticism that will generally discover the estimations of a work either within the work itself or indistinguishably related to the work, whereas Platonic criticism implies a moralistic criticism. This research paper discusses Criticism in English Literature.